Odpowiedź :
Odpowiedź:
1 + x (x+4) x =-11 |-11
x=0
reszty n8e wjem ale to na pewno jest dkcezwy
1. 1+x(x+4)=1+ x^2+4x dla x=-11
1+ (-11)^2+ 4• (-11)= 1+ 121-44= 78
2. x-2y dla x=1 y=-1
1–2•(-1)= 1+2=3
3. (2x)^2-y(x+1)=4x^2-yx-y dla x=-2 y=5
4•(-2)^2-5•(-2)-5= 4•4+10-5=16+10-5=21
4. (m+1)(n-2)= mn-2m+n-2 dla m=2 n=1
2•1-2•2+1-2=2-4+1-2=-3
Sprowadzasz do najprostszej postaci i dopiero podstawiaj liczby
1+ (-11)^2+ 4• (-11)= 1+ 121-44= 78
2. x-2y dla x=1 y=-1
1–2•(-1)= 1+2=3
3. (2x)^2-y(x+1)=4x^2-yx-y dla x=-2 y=5
4•(-2)^2-5•(-2)-5= 4•4+10-5=16+10-5=21
4. (m+1)(n-2)= mn-2m+n-2 dla m=2 n=1
2•1-2•2+1-2=2-4+1-2=-3
Sprowadzasz do najprostszej postaci i dopiero podstawiaj liczby